Optimal Tourism Development - Campos-Soria, Juan A. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The early days of tourism development had a naïve vision of tourism's impacts on society in terms of economic, social, and environmental benefits. Time has passed, and we have learnt lessons regarding the success and failure of tourism development. Mass tourism development has pros and cons and is not necessarily the optimal development model. Alternative development strategies should be contemplated. This Special Issue deals with different topics concerning optimal tourism development. Destination management requires further understanding of different issues, such as carrying capacity, income-based optimal supply size, identification and development of optimal market niches, and adaptation or environmental protection strategies. Tourism planning is concerned with the role of economies of agglomeration, i.e., the advantages of spatial clusters vs scattered development. Additionally, support for and investment in innovation, accessibility, and mobility are relevant nowadays. From the stakeholders' perspective, it is relevant to discuss ways of cooperating and sources of conflicts among different sectors and actors, governance and incentives for sustainable tourism practices, and equity and economic distribution of benefits. Finally, the development of methodological tools for the assessment of optimal tourism development is necessary for policy making, in particular the development of methods that are capable of integrating economic, environmental, and social criteria.